INSIGHTS ON AROMATASE IMMUNOHISTOCHEMISTRY: VARIATIONS BETWEEN INTRINSIC MOLECULAR SUBTYPES OF BREAST CANCERS - Armasu, I. (Acta Endocrinol (Buchar), 2020)
CONTEXT: Aromatase is a key enzyme in local estrogen production by androgen conversion, especially in women post-menopause. There have been controversies concerning aromatase localization in breast carcinomas and its association with current histopathological variables. MATERIAL AND METHODS: Using polyclonal antibody immunohistochemistry we assessed (by intensity and percentage scores) the immunolocalization of aromatase in 70 tissue samples, and described particularities within the molecular subtypes of breast cancer. RESULTS: Aromatase was found in all tissue compartments: tumor (95.7%), stroma (58.6%) and adipose tissue (94.3%). Aromatase expression in tumor cells correlated inversely with tumor grading (p=-0.361, p=0.027), and positively with estrogen receptor status (ER, p=0.143, p<0.001). Dividing the study group by intrinsic subtypes, a strongly inversely association between tumor aromatase and grading (p=-0.486, p<0.001), and between stromal aromatase and Ki67-index (p=-0.448, p=0.048) was observed in luminal A breast cancer. Tumor aromatase and ER percentage scores had stronger correlations in luminal B HER2 negative (p=0.632, p=0.002), and positive (p=0.324, p=0.026) tumors. In contrast, in triple negative tumors, a positive association stromal aromatase and Ki67 index (p=-0.359, p=0.007) was observed. CONCLUSION: Local aromatase was linked to better tumor differentiation and proliferation in luminal breast subtypes, and not in triple negative cases, suggesting a potential prognostic role of aromatase in breast carcinomas.